The Effectiveness of HEPA Filters on DNA. (June 2018) - Held, Kara F.; Rundell, Clark; Thibeault, Robert; Ghidoni, Daniel; Magoon, Daniel; Nguyen, Trinh; Fisher, Alyson; Parker, Bretna; Spenlinhauer, Tania; Gordon, Joan; Nesbitt, Steven
Most laboratory techniques are performed in biosafety cabinets (BSCs) to provide contamination control of the experiments. By using specifically directed airflow and high-efficiency particulate air (HEPA) filtration, potential contaminants are removed from the work area within the BSC. Aerosols may be created by common lab practices, such as centrifugation, pipetting, and opening tubes. HEPA filters are very effective at removing various-sized contaminants but do not prevent gases and vapors from penetrating through them. HEPA filters are not effective at all sizes of particles. Researchers have speculated that DNA may not be captured by HEPA filters, allowing for contamination of subsequent experiments by aerosolized DNA. Here we found that DNA is captured by a HEPA filter at the same efficiency as the filter is rated and discovered that DNA cannot be dislodged from a HEPA filter.